The Impact of Ease of Doing Business on Gross Domestic Product among Southeast Asian Countries, 2014-2020 - Arvel Valency Laurens; Edward Wijaya; James Ryan Raharjo; Vasco Constantinus Panglewai; Maichal Maichal (CV Edujavare Publishing, 2026)
This study examines the effect of Ease of Doing Business on economic growth, as measured by Gross Domestic Product (GDP), in Southeast Asian countries. The research problem is the persistent differences in the level of ease experienced among Southeast Asian countries and how this impacts economic performance. This study uses secondary data from the World Bank's GDP and Ease of Doing Business indicators based on the Distance to Frontier (DTF) Score from Doing Business. The indicators include things like starting a business, handling building permits, obtaining electricity, registering property, obtaining credit, paying taxes, trading abroad, and resolving bankruptcy. This study uses a Fixed Effect Model to conduct panel data regression analysis on 9 countries in the Southeast Asian region from 2014 to 2020. The results show that all Ease of Doing Business variables have a significant impact on GDP simultaneously. Bankruptcy Resolution has a negative and significant impact on GDP; partially, Building Permit Management, Electricity Procurement, and Cross-Border Trade have a positive and significant impact on GDP. Meanwhile, starting a business, obtaining credit, paying taxes, and registering property did not have a significant impact. This study found that ease of doing business in certain sectors plays a significant role in increasing economic growth. Therefore, the government recommends improving the effectiveness of regulations, infrastructure, and trade to encourage sustainable economic growth.